2019
DOI: 10.1039/c8md00395e
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of DNA-intercalative naphthalimide-benzothiazole/cinnamide derivatives: cytotoxicity evaluation and topoisomerase-IIα inhibition

Abstract: A new series of different naphthalimide-benzothiazole/cinnamide derivatives were designed, synthesized and tested for their in vitro cytotoxicity on selected human cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Unfortunately this combination was no better than standard treatment 36 . Sankara et al 37 , designed various naphthalimide benzothiazole/cinnamide analogues, all of which showed DNA intercalation, topoisomerase inhibition and low µM cytotoxicity using the MTT assay; however, none showed breast cancer selectivity in MCF-7 cells. Li et al 17 designed various naphthalimide-pyrazolyl derivatives that again showed DNA intercalation properties; the most potent of these showed a slight selectively towards MCF-7 cells (MTT assay 0.7 µM) compared with HeLa (3 µM) and A549 (5 µM) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately this combination was no better than standard treatment 36 . Sankara et al 37 , designed various naphthalimide benzothiazole/cinnamide analogues, all of which showed DNA intercalation, topoisomerase inhibition and low µM cytotoxicity using the MTT assay; however, none showed breast cancer selectivity in MCF-7 cells. Li et al 17 designed various naphthalimide-pyrazolyl derivatives that again showed DNA intercalation properties; the most potent of these showed a slight selectively towards MCF-7 cells (MTT assay 0.7 µM) compared with HeLa (3 µM) and A549 (5 µM) cells.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds 25 and 26 are naphthalimide-benzothiazole derivatives reported by Rao et al [60] as potent topoisomerase-IIα inhibitors. The CDK2 enzyme is mainly responsible for DNA replication, cell division, and cell cycle progression.…”
Section: Topoisomerase Inhibitorsmentioning
confidence: 99%
“…Sankara Rao et al [87] have reported napthalimide-bearing benzothiazole derivatives as potent cytotoxic agents. The synthesized derivatives were screened against a selected panel of cancer Molecular docking studies revealed strong binding interactions within the ATP binding site of human DNA topoisomerase IIα (PDB ID:…”
Section: Phosphatidylinositol-3-kinases (Pi3k)/akt Inhibitorsmentioning
confidence: 99%